Implikasi Pemahaman Tenaga Medis terhadap Hukum Kesehatan dalam Implementasi Clinical Pathway di Ruang Kebidanan RSUD Abepura - Grace Kawengian (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Clinical pathways are essential instruments for ensuring the quality of medical services, patient safety, and legal protection for healthcare workers. However, their implementation continues to face various challenges in healthcare facilities, including in the Obstetrics Ward of Abepura Regional General Hospital (RSUD Abepura). This study aims to analyze the legal implications of non-compliance with clinical pathways and identify the factors that hinder healthcare workers in their implementation. This research employs an empirical legal method using a normative–empirical approach through questionnaires, observations, and document reviews. The results show that most healthcare workers have a strong understanding of the legal obligations related to clinical pathway implementation, with 95% of respondents acknowledging the legal risks associated with failing to follow established standards. Nevertheless, several discrepancies in practice were found, such as performing episiotomy without indication, incomplete clinical pathway documentation, and a lack of integration between manual clinical pathways and electronic medical records. The main barriers identified include high workload, insufficient training, limited facilities, and weak coordination among healthcare personnel. The discussion reveals a gap between legal awareness and operational application. In conclusion, the implementation of clinical pathways is not yet optimal and requires managerial strengthening, enhanced training, improved facilities, and integrated information systems to support compliance and minimize legal risks.